2022
DOI: 10.1024/0300-9831/a000722
|View full text |Cite
|
Sign up to set email alerts
|

The Nutri-Score nutrition label

Abstract: Abstract. Nutri-Score is a front-of-pack nutrition label with summary graded colour-coding, which aims to inform consumers, in a simple and understandable way, of the overall nutritional value of foods, in order to help them to make healthier choices at the point of purchase and to encourage manufacturers to improve the nutritional quality of their products. It is based on a five-colour scale (from dark green to dark orange) associated with letters, from A to E, to optimize logo accessibility and understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 40 publications
1
50
0
2
Order By: Relevance
“…Nevertheless, studies have indicated that subjects with a dietary intake corresponding to a better FSAm-NPS score have a lower consumption of sweet and fatty snacking products, lower saturated fatty acid intakes and higher consumption of fruits and vegetables [ 48 ]. These findings were also observed in our research, suggesting that eating foods that are better ranked on the Nutri-Score scale is associated with better overall dietary nutritional quality [ 18 ]. In addition, a study by De Temmerman et al [ 49 ], which investigated the impact of the Nutri-Score and its five categories on consumers’ perceived perceptions of healthiness and purchasing intentions, found that the presence of the Nutri-Score enabled respondents to better assess the healthiness of food and beverage products.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Nevertheless, studies have indicated that subjects with a dietary intake corresponding to a better FSAm-NPS score have a lower consumption of sweet and fatty snacking products, lower saturated fatty acid intakes and higher consumption of fruits and vegetables [ 48 ]. These findings were also observed in our research, suggesting that eating foods that are better ranked on the Nutri-Score scale is associated with better overall dietary nutritional quality [ 18 ]. In addition, a study by De Temmerman et al [ 49 ], which investigated the impact of the Nutri-Score and its five categories on consumers’ perceived perceptions of healthiness and purchasing intentions, found that the presence of the Nutri-Score enabled respondents to better assess the healthiness of food and beverage products.…”
Section: Discussionsupporting
confidence: 85%
“…Surveys carried out in France, Spain, Belgium and Germany have additionally shown that the Nutri-Score is perceived favourably by consumers. These surveys also found that the Nutri-Score is the preferred format when compared to other nutrition labels tested; this was found to be particularly true in populations with the lowest level of nutritional knowledge [ 18 ]. It should be noted that controversy exists regarding the Nutri-Score and its proposed adoption by the European Union Commission as a front-of-pack labelling system for European Union member states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For four years, major food lobby groups developed various strategies to try to block its application [4,5]. They denied or questioned the results of the abundant scientific studies that demonstrated the effectiveness of Nutri-Score compared to other existing graphical formats [6]. In 2020, the large multi-country FOP-ICE study in 12 European countries including Spain [7,8] showed that the Nutri-Score appeared as the best scheme to help participants identify healthier food products compared to other front-of-pack nutrition labels (FoPLs).…”
Section: Introductionmentioning
confidence: 99%